Effects of a Resistance Training Program on Body Composition and Maximum Strength in University Students According to Their Baseline Body Mass Index [Efectos de Un Programa de Entrenamiento Muscular Sobre la Composición Corporal y Fuerza Máxima en Estudiantes Universitarios Según Su Índice de Masa Corporal Inicial] - Herrera-Valenzuela, T (Sociedad espanola de dietetica, 2021)
Introduction: Resistance training exercises must be adapted to people s characteristics and dosed individually to achieve maximum benefits. Aim: To compare the effects of a resistance training program on body composition and maximum strength in physically active university students, according to their baseline body mass index (BMI). Material and methods: Twenty-four Physical Education students (15 males and 9 females) completed a supervised resistance training program that lasted eight weeks (16 sessions). The students were previously distributed into a group below the mean BMI group (BMG; n = 11; 7 males and 4 females) and above the mean BMI group (AMG; n = 13; 8 males and 5 females). Body weight, height, BMI, body composition (adipose mass and muscle mass), and maximum upper body strength (bench press and military press), and lower body strength (parallel squat [45°] and deadlift) were measured through a one-repetition maximum (1RM). Results: Fat mass decreased significantly (p< 0.05) with a small effect size (d< 0.30) in both groups (BMG and AMG). In contrast, muscle mass increased significantly (p= 0.008) only in AMG with a small effect size (d= 0.36). Maximum upper and lower body strength increased significantly (p< 0.05) with a small and moderate effect size (d< 0.80) in the BMG and AMG. Comparisons between the groups revealed no significant differences. Conclusions: An eight-week resistance training program significantly reduces fat mass and a significant increase in maximal upper and lower body strength in physically active university students, independent of their baseline BMI. However, only AMG achieves a significant increase in muscle mass. © 2021 Sociedad espanola de dietetica. All rights reserved.